PEMETAAN KEMAJUAN LUBANG BUKAAN TAMBANG BAWAH TANAH PT. DEMPO MAJU CEMERLANG, KECAMATAN IV JURAI, KABUPATEN PESISIR SELATAN, PROVINSI SUMATERA BARAT - Hanifa Octaviani; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2023)
Abstract.  PT. Dempo Maju Cemerlang, located in Nagari Tambang IV Jurai District, Pesisir Selatan Regency, West Sumatra Province, is a company engaged in ore (gold) mining. The existence of ore in the exploitation area is in the form of veins (quartz veins) that are elongated and vertical. The mining process of PT. Dempo Maju Cemerlang usesmethods Shrinkage and, Glory Hole namely mining by creating levels. Between the levels are made stopes or rooms. In the process of extracting the ore it is crushed using themethod over hand (digging upwards) and allowed to gather in the stope. Ore mining is carried out in a horizontal incision starting from the bottom leading upwards through a manway. Mapping the progress of the opening holes that will be carried out is using themethod terrestrial with measuring total stations. Themethod terrestrial is a strategy or technique of obtaining data about objects or phenomena on the earth by direct contact or measuring directly on the object or phenomenon of the study. Retrieval of data using themethod terrestrial aims to map the progress of the underground mine openings and will obtain the layout of the underground mine openings of PT. Dempo Maju Cemerlang that can be analyzed and the amount of progress in the underground mine will be known.Keywords: Mapping, Terrestrial, Mining Progress, Total station